Splenic Artery Aneurysm Following Endoscopic Ultrasound Guided Fine-Needle Aspiration: A Rare Complication Presenting with Delayed Massive Gastrointestinal Bleeding - Aykut, Hüseyin; Ordu, Baver; Dertsiz, Berkay; Saruhan, Mehmet Ali; Adalı, Gupse (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Aykut H, Ordu B, Dertsiz B, Saruhan MA, Adalı G. Splenic artery aneurysm following endoscopic ultrasound guided fine-needle aspiration: A rare complication presenting with delayed massive gastrointestinal bleeding. Turk J Gastroenterol. Published online November 3, 2025. doi:10.5152/tjg.2025.25457